Contract of Suretyship in Nepal: Analysis with Provisions and Precedents - Kalika, Satya Narayan (Management Dynamics, 2021)
The superstructure of guarantee contract stands on the basis of the Surety who takes responsibility of principal debtor and ensures to perform liability to the Creditor in case the debtor defaults. The purpose of this study is to analyze the role of surety in the contract of suretyship on the basis of legal frameworks and judicial decisions of Supreme Court of Nepal and common law countries. As a doctrinal Research, it will adopt exploratory doctrinal and analytical research design. It is based on the doctrinal sources. It uses the qualitative data; collected from both primary as well as secondary sources of law.